2021
DOI: 10.3389/fpsyg.2021.734414
|View full text |Cite
|
Sign up to set email alerts
|

Social and Professional Impact of Learning Communities Within the Alliances for Graduate Education and the Professoriate Program at Michigan State University

Abstract: At Michigan State University (MSU), the AGEP learning community features the participation of over 70% of the African-American, Latinx, and Native-American under-represented minorities (URM), also referred to as Black, Indigenous, and People of Color (BIPOC) doctoral students in fields sponsored by the National Science Foundation (NSF). Monthly learning community (LC) meetings allow AGEP participants to create dialogues across disciplines through informal oral presentations about current research. The learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Davis et al (2012) explored the factors that influence female university students to pursue graduate studies using logistic regression model and found that peer experience produces higher degree expectations, and one additional unit of peer experience increases the intent to pursue graduate studies by 3.5%. In fact, positive interactions reinforce students' performance and aspirations, resulting in higher educational expectations for each group (Pascarella, 1985;Hubbard, 2005;To et al, 2014;Thomas et al, 2021).…”
Section: Influencing Factors For Pursuing An MDmentioning
confidence: 99%
“…Davis et al (2012) explored the factors that influence female university students to pursue graduate studies using logistic regression model and found that peer experience produces higher degree expectations, and one additional unit of peer experience increases the intent to pursue graduate studies by 3.5%. In fact, positive interactions reinforce students' performance and aspirations, resulting in higher educational expectations for each group (Pascarella, 1985;Hubbard, 2005;To et al, 2014;Thomas et al, 2021).…”
Section: Influencing Factors For Pursuing An MDmentioning
confidence: 99%
“…In contrast,Reichenberger and Raymond (2021) chose a Bourdieusian career capital framework to examine how tourism students in New Zealand were adapting their career strategies to a 'career shock' context.Examples of UK frameworks include the 2013 Solent Capital Compass from Southampton Solent University, which comprises 16 elements categorised as Capabilities/Human Capital, Confidence/Psychological Capital and Connections/Social Capital(Whistance & Campbell 2018) and the widely-cited Graduate Capital Model from the nearby University of Southampton, which conceptualises employability as 'constituting a range of dynamic, interactive forms of capital which are acquired through graduates' lived experiences', namely Human Capital, Social Capital, Cultural Capital, Identity Capital and Psychological Capital(Tomlinson 2017, p. 340). Tomlinson's model has been used with a range of student and graduate populations in the UK, US, Australia and China, including socioeconomically diverse undergraduates, minority doctoral students, industry internship candidates and international graduate migrants and returnees(Parutis & Howson 2020;Thomas et al 2021;Benati & Fischer 2021;Pham, Tomlinson & Thompson 2019;Singh & Fan 2021).…”
mentioning
confidence: 99%